VISITOR MANAGEMENT A SINEQUANON FOR DEVELOPMENT OF FESTIVAL TOURISM IN ABUJA: GEOGRAPHICAL INFORMATION SYSTEM IS APPROACH - Abomeh, Ofobruku Sylvester; Blessing C., Iheabunike Okafor (European Scientific Journal, ESJ, 2014)
This study discusses how geographic information system technology could serve as bases for visitors’ management in the development of festival tourism in ABUJA. GIS functionality was used to create digital spatial database for tourist site, hotels, hospital, police station and road network for tourist (visitors) movement within ABUJA. The study involved the design of spatial database for various entities identified in the study area. Geometric data was acquired from satellite imagery through digitizing and the imagery updated through hand-held GPS receiver while attribute data were acquired through social survey. ARCGIS 9.3 was used for database creation where attribute tables were linked with geometric data. Various spatial operations were performed and these include Buffering, Spatial query and Network Analysis (best routes, alternative route and closest facility) to efficiently map tourist (visitors) movement in ABUJA. ArcGIS9.3 provides greater support in giving information about tourist sites and solving routs directions finding problems. The study was concluded by recommending various ways in applying GIS to promptly identify cultural and tourism sites, managing tourist (visitors) movement and solving directions finding problems for visitors’ management in festival tourism development in ABUJA.